Mononchida (Nematoda) from Silent Valley National Park, India - Nusrat, Tabinda; Anjum, Ashher; Ahmad, Wasim (Zootaxa, 2013)
Four known and a new species of nematodes belonging to the Order Mononchida Jairajpuri, 1969 are described and illustrated from Silent Valley National Park, India. Cobbonchus vulvastriatus n. sp. has 0.92–0.11 mm long body; buccal cavity 25–27×12–13 μm, dorsal tooth comparatively large with its apex at 72–81% from base of stoma; subventral teeth slightly smaller with their apices at 40–41% from the base of stoma; female genital system amphidelphic, 1–3 pre-vulval and 2–4 post-vulval cuticular infoldings present; spicules 1.2–1.4 times the cloacal body diameter long; gubernaculum trough-shaped with distal thickening; lateral guiding pieces small; ventromedian supplements six, spaced; tail conoid, curved ventrad with a strong angular bending, slender portion of tail about twice the anterior part; caudal glands well developed, arranged in tandem, spinneret terminal. Clarkus sheri (Mulvey, 1967) Jairajpuri, 1970; Mylonchulus amurus Khan & Jairajpuri, 1979; Mylonchulus mulveyi Jairajpuri, 1970 and Mylonchulus paraindex Ahmad, Baniyamuddin & Jairajpuri, 2005 are recorded for the first time from this park.